If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-5x + 6) = 72 Reorder the terms: 2(6 + -5x) = 72 (6 * 2 + -5x * 2) = 72 (12 + -10x) = 72 Solving 12 + -10x = 72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -10x = 72 + -12 Combine like terms: 12 + -12 = 0 0 + -10x = 72 + -12 -10x = 72 + -12 Combine like terms: 72 + -12 = 60 -10x = 60 Divide each side by '-10'. x = -6 Simplifying x = -6
| (7w-5)(6w+6y-1)= | | 9a+3b=2 | | (x+25)+3x+95+80=360 | | 5(1x+10)=65 | | 2(x-7)-10=12-4 | | -5X+8Y=30 | | 5(4x+12)=35 | | C/5-4=7 | | 40p^2=28-36p | | 3=5cosx | | 40p^2=28-369 | | 6(x-3)+10=4x+4 | | x=3/(4y-1) | | 6+10k=56 | | (-t/3)^2 | | .817= | | -c/-5=-12 | | 2x^2-25=5x | | 15mn(-4m+6mn-10n)= | | -r/2=13 | | -0.3(0.7x-0.9)=-1.89 | | y/2-9/5=9x-8/3 | | T/-4=-20 | | 50-5T=15 | | 7x+40=16 | | -2/3w=6 | | -5(x-3)-(2x+7)= | | y=lx+3l-1 | | 3/16x4/9 | | 24+2x=3x+48 | | (X+7)-8=12 | | 2e^3x=30 |